Exome Analysis Identified Novel Homozygous Splice Site Donor Alteration in NT5C2 Gene in a Saudi Family Associated With Spastic Diplegia Cerebral Palsy, Developmental Delay, and Intellectual Disability - Naseer, Muhammad Imran; Abdulkareem, Angham Abdulrahman; Pushparaj, Peter Natesan; Bibi, Fehmida; Chaudhary, Adeel G. (Frontiers in Genetics, 2020)
Hereditary spastic paraplegias (HSPs) is a rare heterogeneous group of neurodegenerative diseases, with upper and lower limb spasticity motor neuron disintegration leading to paraplegias. NT5C2 gene (OMIM: 600417) encode a hydrolase enzyme 5'-Nucleotidase, Cytosolic II play an important role in maintaining the balance of purine nucleotides and free nucleobases in the spinal cord and brain. In this study we report a novel homozygous splice site donor alteration in NT5C2 gene leading to spastic diplegia cerebral palsy, developmental delay and microcephaly. We have identified a large consanguineous Saudi family segregating developmental delay, spastic diplegia cerebral palsy and intellectual disability along with intellectual disability. Whole exome sequencing (WES) was performed for the affected members of the family to study the novel mutation. WES data analysis, confirmed by Sanger sequencing analysis, identifies a homozygous splice site donor alteration of possible interest in NT5C2 (ENST00000343289: c.539+1G>T). The mutation was further ruled out in 100 healthy control from normal population. The novel homozygous mutation observed in this study has not been reported in the literature or variant databases. In conclusion, the here detected homozygous mutation in the intronic region of NT5C2 gene. Further explain the possibility that NT5C2 gene may play important and essential role for normal human neurodevelopment.